Patriarchal Dominance in Virginia Woolf's Mrs. Dalloway, To the Lighthouse, and The Waves: A Study of the Female Characters - Khrisat, Abdulhafeth Ali (Mediterranean Journal of Social Sciences, 2012)
This paper aims to analyze and clarify patriarchal dominance in the Victorian era as described by Virginia Woolf's threenovels, Mrs. Dalloway (1925), To the Lighthouse (1927), and The Waves (1930). Woolf revolts against the patriarchal behavior ofdominance that treats women as prisoners during that age. The view of the feminist approach is that women are portrayed as sociallyand economically dependent in a society with male hegemony. Moreover, society has dealt with gender in a way that harms women intowhich men are trained to believe that they are superior to them. Woolf declares her revolt against women as prisoners of reality. Woolfstands against the popular image of her age _ the woman is devoted to be submissive to her husband. The female characters struggleto free themselves from restraint, seeking purpose and agency in the world through interaction with men. Throughout the analysis offemale characters, Woolf contested the inferior situation of women in the Victorian age. The female characters' words, speeches, andinterior monologues reveal that their pain, sadness and loneliness are because of the patriarchal dominancy.